Growth Response of Sweet Potato (Ipomoea Batatas L.) to Application of Selected Indigenous Plant Growth- Promoting Rhizobacteria and Nitrogen Fertilization - Farazana Yasmin, (2007)
Sweetpotato requires high amount of fertilizer for commercial cultivation which can lead to increase production cost and environmental pollution. Biofertilizer is globally accepted as an alternative source of chemical fertilizer which improves plant growth through increased uptake of water and mineral nutrients. Laboratory and field experiments were conducted to characterize the beneficial properties of plant growth-promoting rhizobacterial (PGPR) strains isolated from sweetpotato rhizosphere and to determine the effects of rhizobacterial inoculation on the growth and yield of sweetpotato. Performance of the PGPR with different levels of nitrogen fertilizer on plant growth was evaluated under field condition. In vitro scanning electron microscopy (SEM) and transmission electron microscopy (TEM) studies were conducted to examine the colonization of PGPR strains on roots of sweetpotato plantlets.Results of the laboratory study showed that 15 rhizobacterial isolates were able to produce indole acetic acid (IAA). The concentration of IAA produced ranged from 3.84 to 13.33 mg L-1. Addition of L-tryptophan (L-TRP) to the bacterial isolates increased the production of IAA ranging from 4.94 to 46.66 mg L-1. Six isolates (40%) were able to solubilize insoluble phosphate as evident by production of clear zone on calcium phosphate medium. All isolates were able to grow in N-free media indicating their abilities to produce nitrogen which ranged from 0.74 to 1.32 ppm. Three of the isolates produced fluorescent pigment on agar plate indicated their abilities to produce siderophores. Four isolates were able to inhibit the fungal pathogens Rhizoctonia sp. and Pythium sp. The intrinsic antibiotic test showed that all isolates were resistant against Chloramphenicol (10 and 30 μg mL-1), Streptomycin (10 μg mL-1), Kanamycin (5 and 30 μg mL-1), Penicillin (10 μg mL-1) and Tetracyclin (30 μg mL-1). The Biolog identification system identified the rhizobacterial isolates UPMSP2, UPMSP3, UPMSP9, UPMSP10, UPMSP12, UPMSP13, UPMSP18 and UPMSP20 as Pseudomonas corrugate, Serratia ficaria, Klebsiella terrigena, Erwinia cypripedii, Acinetobacter radioresistens, Pseudomonas maculicola, Paenibacillus pabuli and Pseudomonas fuscovaginae, respectively. Inoculation of Sepang Oren sweetpotato cultivar with twelve rhizobacteria isolates under glasshouse condition positively affected plant growth. The highest growth was observed on plants inoculated with Klebsiella sp. which increased shoot dry weight by 23% compared to control. Five of the isolates were able to produce sweetpotato storage roots. Klebsiella sp and Erwinia sp. produced higher storage root yields of 35.15 and 8.22 g plant-1, respectively, compared to the other treatments. PGPR inoculation significantly increased the concentrations and uptake of N, P, K, Ca and Mg in plant tissue, total bacterial populations, soil pH, IAA and nutrients (N, P, K, Ca and Mg) concentrations. Scanning electron microscopy (SEM) and transmission electron microscopy (TEM) studies showed that Klebsiella sp, Erwinia sp, Azospirillum brasilense, Bacillus sphaericus UPMB10 could effectively colonize the sweetpotato root surface and internal region of 7 day old plantlets. Field inoculation of five bacterial strains in combination with three levels of nitrogen fertilizer (0, 33, and 100 kg N ha-1) in the form of urea significantly (P<0.05) influenced growth and storage root yield of Sepang Oren sweetpotato. The highest storage root yield (12.59 kg plot-1) was observed in plants inoculated with Klebsiella sp. applied with 33 kg N ha-1. Significant interaction between PGPR inoculation and N fertilization was observed on the uptake of N, K and Ca in shoots. Bacterial Inoculation and N fertilization significantly stimulated the soil bacterial population at various stages of plant growth. The highest population of 2.63X107 CFU g (dry wt.)-1 soil was observed in soil inoculated with Klebsiella sp. applied with 33 kg N ha-1. However, the population of bacteria in soil declined after the 2nd and 3rd month of inoculation.